Multifunctional polymer nanocomposites with enhanced mechanical and anti-microbial properties. (October 2015) - Quaresimin, M.; Bertani, R.; Zappalorto, M.; Pontefisso, A.; Simionato, F.; Bartolozzi, A.
Abstract: The paper reports the results of a project aiming to obtain multifunctional binary and ternary polymer nanocomposites with enhanced mechanical and anti-microbial properties. To this end a DGEBA-based epoxy resin is loaded using montmorillonite clays and later used as matrix for glass fibre reinforced laminates. Both binary and ternary nanomodified specimens are manufactured and subjected to mechanical testing. An accurate analysis of the effect of nanomodification on the biological activity is carried out as well. Highlights: Results from nanocomposites with enhanced mechanical and anti-microbial properties are presented. Epoxy is loaded with nanoclays and used as matrix for glass fibre reinforced laminates. Binary and ternary nanomodified specimens are manufactured and tested. The effect of nanomodification on the biological activity is studied.